Optimización del sistema de bombeo mecánico para máxima eficiencia de levantamiento en tres pozos que presenten interferencia por gas en el campo Palagua (2020)
This work uses real data from 3 wells of the Palagua field, located in Puerto Boyacá, operated by the IJP Temporary Union. The main results were, to give better gas handling and avoid gas interference in the wells, one of the two possible cases of optimization was to increase the efficiency of the pump as a compressor by decreasing dead spaces and the other approach was the installation of a cup-type separator at the bottom in order to prevent the entry of gas to the pump and as main conclusions the decrease of dead space in wells with little gas presence becomes more profitable, otherwise, in wells with high ratio Gas oil is much more practical collation of gas separators in the background.